2016
DOI: 10.1007/s12640-016-9670-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress

Abstract: Severe hand-foot-and-mouth disease (HFMD) caused by Enterovirus 71 (EV71) always accompanies with inflammation and neuronal damage in the central nervous system (CNS). During neuronal injuries, cell surface-exposed calreticulin (Ecto-CRT) is an important mediator for primary phagocytosis of viable neurons by microglia. Our data confirmed that brainstem neurons underwent neuronophagia by glia in EV71-induced death cases of HFMD. EV71 capsid proteins VP1, VP2, VP3, or VP4 did not induce apoptosis of brainstem ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…In the present study, we demonstrated that VP1 plays a promotive role in MSC autophagy (Fig. 2), which is consistent with our previous findings(25). However, the effect of VP1-induced autophagy on MSC survival still remains unclear because autophagy plays dual roles in the nervous system.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, we demonstrated that VP1 plays a promotive role in MSC autophagy (Fig. 2), which is consistent with our previous findings(25). However, the effect of VP1-induced autophagy on MSC survival still remains unclear because autophagy plays dual roles in the nervous system.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, in an EV71-infected mouse model, VP1 was found co-localized with LC3 and/or autophagosome-like vesicles in neurons, and VP1 expression was positively correlated with LC3-II expression, aggregation and autophagosome formation(24). Upregulation of LC3-II expression was also observed in VP1-transfected HEK293 cells(25). Considering the regulatory role of VP1 in both MSC autophagy and PMP22 expression (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some reported cases of neuronophagia may be neurophagy. For example, there are multiple reports of neuronophagia in brains infected with different viruses, including the hand‐foot‐and‐mouth disease enterovirus 71, where viral infection resulted in exposure of calreticulin on neurons that were apparently eaten alive by glia . This raises the possibility that one of the functions of neuronophagia and neurophagy is to remove and destroy virally infected neurons to prevent spread of the virus.…”
Section: Neuronophagiamentioning
confidence: 99%
“…Virus infection could induce autophagy, and many viral proteins can induce autophagy also [37][38][39][40]. A recent study showed that neither 2B, 2C, 3A, 3B, 3AB, 3C nor 3D could trigger autophagy individually [7].…”
Section: Discussionmentioning
confidence: 99%